Collections in the English National Museums: The Numbers - Suzanne Keene (Papers from the Institute of Archaeology, 2007)
The DCMS (Department of Culture Media and Sport) commissioned a report in 2002, delivered in 2003, from consultants PKF, on the storage of the collections of the national museums. Their report and a paper based on it, compiled by the DCMS in 2004, was obtained under the Freedom of Information Act. The intention in this article is rather to investigate the usefulness or lack of these statistics and to understand what issues should be taken account of in any future investigation. Although most of the data are problematic to interpret due to the questions asked in data collection, some useful statitics are provided including on the general quantification of collections in the English national museums. The figures illustrate the magnitude of and variation between collections, and confirm observations from real life on the corresponding variation in storage requirements.